2021
DOI: 10.3390/jcdd8110146
|View full text |Cite
|
Sign up to set email alerts
|

Better Medications Adherence Lowers Cardiovascular Events, Stroke, and All-Cause Mortality Risk: A Dose-Response Meta-Analysis

Abstract: Aims: We investigated the association between vascular medication adherence, assessed by different methods, and the risk of cardio-cerebrovascular events and all-cause mortality. Methods: A meta-analysis with a systematic search of PubMed, Web of Science, EMBASE, and Cochrane databases from inception date to 21 June 2021 was used to identify relevant studies that had evaluated the association between cardiovascular medication adherence levels and cardiovascular events (CVEs), stroke, and all-cause mortality ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
11
1
1
Order By: Relevance
“…The increasing risks of stroke-related events and all-cause mortality in our study were similar to the previous meta-analyses on assessments of medication adherence to statins [ 21 ], antihypertensives [ 22 ], and/or cardiovascular medications [ 15 , 16 ]. Although these studies focused on the risks of stroke-associated outcomes linked to medication adherence, they did not consider the impacts of other disease risk factors.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The increasing risks of stroke-related events and all-cause mortality in our study were similar to the previous meta-analyses on assessments of medication adherence to statins [ 21 ], antihypertensives [ 22 ], and/or cardiovascular medications [ 15 , 16 ]. Although these studies focused on the risks of stroke-associated outcomes linked to medication adherence, they did not consider the impacts of other disease risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies demonstrated that medication adherence is essential in stroke management to reach optimal clinical outcomes [ 14 ]. Previous meta-analyses reported that higher adherence to cardiovascular medications was associated with a decreased risk of coronary heart disease, stroke, and all-cause mortality [ 15 , 16 ]. Although medication adherence benefits patients at risk of stroke, around forty to fifty percent of patients do not take their cardiovascular medications as prescribed [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, optimal adherence was associated with significantly reducing cardiovascular events and mortality. A recent meta-analysis indicated that each incremental 20% increase in adherence level of cardiovascular medication reduced the risk of cardiovascular events by 9%, stroke by 16%, and all-cause mortality by 10% [39]. Several clinical studies highlighted the benefits of cardiovascular medications and the importance of adherence to prescribed medications to optimize health outcomes.…”
Section: Medication Adherence-related Outcomes 41 Clinical Outcomesmentioning
confidence: 99%
“…Good adherence reduces the risk of fatal or non-fatal coronary heart disease, stroke or sudden cardiac death [ 25 ]. Liu et al performed a meta-analysis of 46 articles to assess for a dose response between CV medication adherence, CV events and all-cause mortality [ 26 ]. Data were available for 4,051,338 unique patients, average age 60.1 years, 44% female.…”
mentioning
confidence: 99%